The relationship between public listing, context, multi-nationality and internal CSR - Goergen, Marc; Chahine, Salim; Wood, Geoffrey; Brewster, Chris (Elsevier, 2019)
Are MNEs more socially responsible, and where is this more likely to occur? Are firms less responsible in emerging or transitional economies, and what impact does the dominant national corporate governance regime have? We explore the association between public listing and the existence of a CSR code within specific institutional settings and assess whether MNEs are any different to their local counterparts, based on an internationally comparative survey. We find that listed firms as well as firms from civil law countries are more likely to have CSR statements. MNEs are also more likely to have CSR statements, independent of their country of origin. While we find consistent evidence of a correlation between the existence of a CSR statement and investment in staff training, the correlation between the former and employee-friendly HRM is weaker
Keywords: Corporate governance; Legal institutions; Corporate social responsibility (CSR); MNEs; Country of domicile pressures; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura